2006
DOI: 10.1293/tox.19.111
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis in Carcinogenicity of Non-genotoxic Carcinogens

Abstract: Abstract:Recently the idea of hormesis, a biphasic dose-response relationship in which a chemical exerts opposite effects dependent on the dose, has attracted interest in the field of carcinogenesis. With non-genotoxic agents there is considerable experimental evidence in support of hormesis and the present review highlights current knowledge of doseresponse effects. In particular, several in vivo studies have provided support for the idea that non-genotoxic carcinogens may inhibit hepatocarcinogenesis at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 88 publications
2
7
0
1
Order By: Relevance
“…In addition, considerable attention was directed toward assessing the underlying mechanisms that could account for the enhanced cancer risk at high dosages and the reduced cancer risks below threshold dosages in the hormetic dose‐response range. The quantitative features of the dose responses in the series of papers published by the Japanese investigators generally were consistent with those reported within the hormesis database [115,116,119,120]. In contrast to the lack of mention by the SOT expert panel in 1981 [121] of the term hormesis for the responses of 2‐AAF in terms of bladder cancer incidence, the Japanese investigators viewed their findings as being manifestations of hormetic dose response.…”
Section: Do Epigenetic Carcinogens Act Hormetically?supporting
confidence: 64%
See 1 more Smart Citation
“…In addition, considerable attention was directed toward assessing the underlying mechanisms that could account for the enhanced cancer risk at high dosages and the reduced cancer risks below threshold dosages in the hormetic dose‐response range. The quantitative features of the dose responses in the series of papers published by the Japanese investigators generally were consistent with those reported within the hormesis database [115,116,119,120]. In contrast to the lack of mention by the SOT expert panel in 1981 [121] of the term hormesis for the responses of 2‐AAF in terms of bladder cancer incidence, the Japanese investigators viewed their findings as being manifestations of hormetic dose response.…”
Section: Do Epigenetic Carcinogens Act Hormetically?supporting
confidence: 64%
“…This question has been investigated in considerable detail by Japanese investigators using a variety of epigenetic carcinogens [115–119]. In general, these investigators reported that when studied over a very broad dosage range, the responses at high dosages increase the occurrence of tumors and/or liver foci formation, which is an excellent predictive marker for liver tumor development.…”
Section: Do Epigenetic Carcinogens Act Hormetically?mentioning
confidence: 99%
“…In addition, considerable attention was directed toward assessing the underlying mechanisms that could account for the enhanced cancer risk at high dosages and the reduced cancer risks below threshold dosages in the hormetic dose-response range. The quantitative features of the dose responses in the series of papers published by the Japanese investigators generally were consistent with those reported within the hormesis database [115,116,119,120]. In contrast to the lack of mention by the SOT expert panel in 1981 [121] of the term hormesis for the responses of 2-AAF in terms of bladder cancer incidence, the Japanese investigators viewed their findings as being manifestations of hormetic dose response.…”
Section: Do Epigenetic Carcinogens Act Hormetically?supporting
confidence: 62%
“…This question has been investigated in considerable detail by Japanese investigators using a variety of epigenetic carcinogens [115][116][117][118][119]. In general, these investigators reported that when studied over a very broad dosage range, the responses at high dosages increase the occurrence of tumors and/ or liver foci formation, which is an excellent predictive marker for liver tumor development.…”
Section: Do Epigenetic Carcinogens Act Hormetically?mentioning
confidence: 99%
“…Cancer can also be initiated due to continued stimulatory processes, which generate multiple mutations in single or multiple cells. Kinoshita et al 2006 have discussed the implications of hormesis in carcinogenesis. This murky area needs crystal clear analytical foundations to develop a drug dose-based effective therapy for routine clinical practice.…”
Section: Beyond Hormesismentioning
confidence: 99%